Best Method using system of equations

x=4y+8

2x-8y=-3

x=4y+8

2x-8y=-3

In this case, since one equation is in the form of x=, substitution would be best for this problem. Simply plug in 4y + 8 in place of x in the second equation, solve for y, then plug that value into the first equation to find x.

X=4y+8

2x-8y=-3

lets use the substitution method

2x-8y=-3

2(4y+8)-8y=-3

8y+16-8y=-3

16 is not equal to -3 so lets try elimination

x=4y+8

2x-8y=-3

xhange the 1st equation to standard for

x-4y=8

2x-8y=-3

multiply the 1st equation to remove x

2x-8y=8

2x-8y=-3

0 is not equal to 11

therefore we cannot solve using both equations so te question’s answer is undefined

RELATED: